GIS UNTUK PEMETAAN KEBISINGAN MENGGUNAKAN CLASSIFIER MODEL - Joniwarta Joniwarta; Dwi Budi Srisulistiowati (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2017)
Noise is an undesirable sound from a business or activity in a certain level and time that can cause public health problems and environmental comfort. Noise occurs because there is a noisy source, a material delivery medium or air. The impact of noise in an area is of great influence to the health and well-being of people, animals and wildlife and disturbance to the natural ecosystem. For human health, noise can cause disturbances in the system of hearing and digestion, stress, headache, increased blood pressure and can reduce performance. Equipment used to conduct this research one of them is the Sound Level Meter which is the main tool in noise research. This tool is downloaded from the playstore app. SLM is used to measure noise intensity. The SLM used is a digital SLM capable of measuring effective sound pressure levels in decibels (dB). This tool measures noise with a scale between 30 ~ 100 dB. This research used qualitative method by conducting survey to Jl KH. Noer Ali West Bekasi to Jl. Wisma Asri Park Bekasi Utara. In this study using GIS with data collection method using Data Mining in Hierarchical clustering.